Dynamic Ideology of Traditionality in Developing Holy Places at Hindus Family in Cakranegara Territory Mataram City - I Wayan Ardhi Wirawan (Satya Widya: Jurnal Studi Agama, 2020)
This study aims to examine the dynamics of traditionality ideology in building holy place among Hindus families in Cakranegara territory, Mataram city. This research was designed in the type of interpretative qualitative research using a case study model. Data collection techniques through observation, interviews, and documentation. Data were analyzed through the stages of classification, reduction, and interpretation. Tri angulation techniques, both tri angulation methods and tri angulation of data sources were used to check the validity of the data. The results showed that the dynamics of traditional ideology in building holy place of Hindu families had been indicated by transformation of cultural traditions at Hinduism practices in four dimensions. First, the position of placing the holy place later no longer applies traditional concepts in a rigid and standard manner. Second, with regard to the spatial size in the construction of holy place in at Hindu families is no longer fixed on the size of the spatial layout that is traditionally applied but adjusted to the situation and condition of karang paumahan (area of home). Third, the form of holy has adapted to the inclusion of external culture. Fourth, the number of pelinggih (holiy place buildings) tends to decrease, especially in the relatively small area of home. Keywords: dynamics, traditionality ideology, holy place, Hindu families.